Handbook of research on computational intelligence for engineering, science, and business - Bhattacharyya, Siddhartha, 1975-.; Dutta, Paramartha; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
'This book discusses the computation intelligence approaches, initiatives and applications in the engineering, science and business fields, highlighting that computational intelligence as no longer limited to computing-related disciplines and can be applied to any effort which handles complex and meaningful information'--Provided by publisher.
Computational intelligence using type-2 fuzzy logic framework / A. Neogi, A.C. Mondal, S.K. Mandal -- Soft computing based statistical time series analysis, characterization of chaos theory, and theory of fractals / Mofazzal H. Khondekar ... [et al.] -- Machine intelligence using hierarchical memory networks / A. P. James -- Image analysis and understanding based on information theoretical region merging approaches for segmentation and cooperative fusion / Felipe Calderero, Ferran Marqu -- Multilevel image segmentation by a multiobjective genetic algorithm based OptiMUSIG activation function / Sourav De, Siddhartha Bhattacharyya, Susanta Chakraborty -- A novel fuzzy rule guided intelligent technique for gray image extraction and segmentation / Koushik Mondal -- Graph based segmentation of digital images / B.K. Tripathy, P.V.S.S.R. Chandra Mouli -- Development of a stop-line violation detection system for Indian vehicles / Satadal Saha, Subhadip Basu, Mita Nasipuri -- A comparative study of unsupervised video shot boundary detection techniques using probabilistic fuzzy entropy measures / Biswanath Chakraborty, Siddhartha Bhattacharyya, Susanta Chakraborty -- A hierarchical multilevel image thresholding method based on the maximum fuzzy entropy principle / Pearl P. Guan, Hong Yan -- Adaptive median filtering based on unsupervised classification of pixels / J. K. Mandal, Somnath Mukhopadhyay -- Data clustering algorithms using rough sets / B.K.Tripathy, Adhir Ghosh -- Evolution of genetic algorithms in classification rule mining / Dipankar Dutta, Jaya Sil -- Database anonymization techniques with focus on uncertainty and multi-sensitive attributes / B. K. Tripathy -- Using data masking for balancing security and performance in data warehousing / Ricardo Jorge Santos, Jorge Bernardino, Marco Vieira -- Schedulers based on ant colony optimization for parameter sweep experiments in distributed environments / Elina Pacini, Cristian Mateos, Carlos Garc Garino -- Particle swarm optimization algorithm and its hybrid variants for feature subset selection / Basabi Chakraborty -- An evolving system in the text classification problem / Elias Oliveira ... [et al.] -- Fuzzy based modeling, control, and fault diagnosis of permanent magnet synchronous generator / N. Selvaganesan -- Algorithms and principles for intelligent design of flapping wing micro aerial vehicles / Ajay Bangalore Harish, Dineshkumar Harursampath -- Fuzzy-controlled energy-conservation technique (FET) for mobile ad hoc networks / Anuradha Banerjee -- Decision Fusion of multisensor images for human face identification in information security / Mrinal Kanti Bhowmik ... [et al.] -- Modernization of healthcare and medical diagnosis system using multi agent system (MAS): a comparative study / Shibakali Gupta, Sripati Mukherjee, Sesa Singha Roy -- Watermarking of data using biometrics / Swanirbhar Majumder, Tirtha Sankar Das -- Quantum backpropagation neural network approach for modeling of phenol adsorption from aqueous solution by orange peel ash / Siddhartha Bhattacharjee, Siddhartha Bhattacharyya, Naba Kumar Mondal -- Computational intelligence for pathological issues in precision agriculture / Sanjeev S. Sannakki ... [et al.] -- Cancer gene expression data analysis using rough based symmetrical clustering / Anasua Sarkar, Ujjwal Maulik -- Computer intelligence in healthcare / Pramit Ghosh ... [et al.] -- Intelligence in web technology / Sourav Maitra, A. C. Mondal -- Performance comparison of different intelligent techniques applied on detecting proportion of different component in manhole gas mixture / Varun Kumar Ojha, Paramartha Dutta.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed December 17, 2012).
Keywords: Computational intelligence; Content analysis (Communication).; Adaptive technologies; Evolutionary computation; Innovative computing systems; Neural networks; Systems engineering; Theoretical and applied sciences